Restarting Method for Hydraulic Turbine Generation Systems Applied PMSG Sensorless Control - Bak, Yeongsu; Lee, Kyo Beum (ICPE 2019 - ECCE Asia - 10th International Conference on Power Electronics - ECCE Asia, 2019)
This paper presents a restarting method for hydraulic turbine generation systems applied permanent magnet synchronous generator (PMSG) sensorless control. The hydraulic turbine generation systems replace a differential pressure control valves (DPCVs) in order to utilize an unused differential pressure (DP) energy in the heat transmission network. The DP control of high-pressure fluids in the heat transmission network is performed through the sensorless control of the PMSG connected to the hydraulic turbine, which is consistently rotated by the high-pressure fluids flowing into the heat transmission network. In these systems, the rotor frequency and position of the PMSG are required for the restarting method. In this paper, the restarting method for the hydraulic turbine generation systems is proposed and it is performed by estimating the rotor frequency and position of the PMSG using the short-circuit current vectors. The effectiveness of the proposed restarting method is verified by simulation results.
Keywords: Differential pressures; Generation systems; Heat transmission; High-pressure fluids; Permanent magnet synchronous generator; Restarting method; Rotor frequency; Rotor position; Permanent magnet synchronous generator (PMSG); Restarting method; Rotor frequency; Rotor position